European Prize for Applied Arts : Monumentality / Fragility. - Cornut, Gaëlle; Schadron, Johanne (Mons : BeCraft/World Crafts Council-Belgique francophone, asbl, 2018)
Vagi, Flora ; Aparicio, Jordi ; Beard, Peter ; Bech-Bruun, Ulla ; Bell, George William ; Bertrand, Cécile ; Biehne, Claudia ; Bijlenga, Marian ; Bolaños-Durman, Juli ; Campo, Kris ; Carré, Sébastien ; Ceulemans, Valérie ; Church, Ray ; Cohn, Gabriela ; Collier, Niki ; Contreras, Trinidad ; Conyard, Eimear ; Danielová, Mária ; De Baets, Karine ; Delarue, Marion ; Delmotte, Francine ; Domingues, Patricia ; Melanin, Dot ; Fawkes, Sally & Jackson, Richard ; Hartel, Ann-Kathrin ; Hartmann, Ariane ; Hoffmann, Dorottya ; Hogan, Joe ; Houdková, Lucie ; Isverding, Melanie ; Jazayeri, Statira ; Kelly, Nicola ; King, Jane ; Kubelková, Zuzana ; Künnap, Julia Maria ; Labordery, Dominique ; Lees, Nicholas ; Lethbridge, James ; Lindahl, Lena ; Lörincz, Réka ; Mälk, Kadri ; Matsuka, Vicktoria ; Morgan, Harry ; Mouyssinat, Nadège ; Nemeth, Susan ; Nes, Janne ; Nimanis, Artis ; Ó Dubhghaill, Cóilín ; Ou, Jiun-You ; Pandikow, Wiebke ; Reinhold, Annemarie ; Richards, Loukia ; Rintaniemi, Päivi ; Romanelli, Bruno ; Rothe, Kristina ; Sarafian, Rita ; Schepens, Helena ; Scholtz, Martin ; Schofield, Caroline ; Seufert, Karin ; Sleire, Astrid ; Solar, Alejandra ; Southgate, Sophie ; Stankov, Dimitar ; Talbot, Anna ; Terajima, Takayoshi ; Toch, Adi ; Van der Leest, Felieke ; Van der Plaats, Ute ; Van Grieken, Reinhilde ; Vanmol, Karen ; Visintin, Graziano ; Walker, Olivia ; Ward, Simon ; Withofs, Fabienne ; Zanella, Annamaria
boek